MITIGATING COORDINATION FRICTIONS IN DEFI: EMPIRICAL EVIDENCE FROM DYNAMIC PANEL MODELS AND EVENT STUDY OF ETHEREUM-BASED PROJECTS - Adedeji Daniel GBADEBO (Gusau Journal of Accounting and Finance)
This study examines the role of crypto funds (CFs) in enhancing the valuation and performance of decentralized digital platforms (DDPs) by mitigating coordination frictions and information asymmetries. Drawing on panel data from 1,200 Ethereum-based projects and event-study evidence around CF investment disclosures, we find that CF-backed DDPs achieve significantly higher token valuations in the primary market, experience positive cumulative abnormal returns (CARs) around investment announcements, and outperform non-CF-backed peers’ post-issuance. The impact of CFs is stronger when they hold central positions in investor networks and when token ownership is more decentralized. Robustness checks using alternative dependent variables, subsample analyses, and interaction terms confirm the validity of the findings. These results highlight the importance of institutional capital not only in financing but also in signaling quality and enhancing governance in decentralized ecosystems. Policy implications include the need for standard CF disclosure practices, token distribution guidelines, and improved audit standards for smart contracts. The findings contribute to emerging debates on institutional legitimacy, valuation dynamics, and governance in the digital asset economy.